Implementasi Manajemen Rantai Pasok dalam Sistem Informasi Pengelolaan Bantuan Tanggap Bencana di Kabupaten Banyumas - Toni Anwar; Rahman Rosyidi; Mulki Ali Mubarok (STMIK Sumedang, 2021)
The Indonesian government has made efforts to channel a lot of aid for those who are directly and indirectly affected. Types of assistance programs from the government are: 1) Village Fund Direct Cash Assistance, 2) Basic Food Assistance for Jabodetabek, 3) Cash Social Assistance, 4) Electricity Fee Waiver, 5) Pre-Employment Cards, 6) Additional Participants for the Family Hope Program and 7) Cards Groceries. Apart from the government, there are also assistance from the community who help each other to alleviate the burdens that were impacted economically during the Covid-19 pandemic. The community provides assistance directly or indirectly. Assistance from the government and society in the form of foodstuffs which must be sufficient for the number of aid recipients. The purpose of this study is to implement SCM (Supply chain management) to assist assistance. The result of this research is a management information system based on supply chain management